A Parallel AGE Method for Parabolic Problems with Special Geometries - Muda, Zaiton; Othman, Mohamed; Chuah, Chin Yew (Universiti Putra Malaysia Press, 1994)
The alternating group explicit (AGE), an explicit iterative method for parabolic problems involving regular domains of cylindrical symmetry is implemented in parallel on a MIMD Sequent S27 system. The AGE method is suitable for parallel computers as it possesses separate and independent tasks, i.e (2 x 2) blocks which can be executed at the same time without interfering with each other. This paper reports the development and implementation of the parallel AGE algorithm. The results from parallel implementation are compared with those of the sequential implementation.